STUDI PENERAPAN PEMBELAJARAN AKSARA JAWA PADA MATA PELAJARAN BAHASA JAWA DI KELAS 5 SEKOLAH DASAR NEGERI BOLOSINGO - Diah Retno Handayani; Heru Arif Pianto; Hasan Khalawi (Universitas Borneo Tarakan, 2025)
The existence of the use of Javanese script in the world of education is increasingly fading. Problems arising from the implementation of Javanese script learning include students' competence in reading and writing Javanese script. This study aims to describe the process of implementing Javanese script learning, the ability to read and write Javanese script, and the obstacles faced in implementing Javanese script learning in the Javanese language subject in grade 5 of Bolosingo State Elementary School. This type of research uses qualitative with an ethnographic study approach. The research data sources are grade 5 students and grade 5 teachers of Bolosingo State Elementary School. Data collection uses observation, interviews, tests, and documentation techniques. Data validity techniques use credibility tests and dependability tests through triangulation of sources, techniques, and time. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. The results of the study show that all grade 5 students have successfully exceeded the minimum passing criteria. The conclusion is that the process of implementing Javanese script learning in grade 5 of Bolosingo State Elementary School has gone according to plan; the ability of grade 5 students in reading and writing Javanese script has developed according to indicators; Obstacles in implementing Javanese script learning at Bolosingo State Elementary School include students' difficulties in distinguishing similar letter shapes and difficulties in reading and writing legendary, pair, and sandhangan scripts.